2005
DOI: 10.1002/art.20870
|View full text |Cite
|
Sign up to set email alerts
|

Cartilage biomarkers in ankylosing spondylitis: Relationship to clinical variables and treatment response

Abstract: Objective. Ankylosing spondylitis (AS) is a progressive disease in which chronic inflammation can lead to extensive new bone formation throughout the spine. At present, few measures of the activity or extent of the disease are available. In this study, we sought to determine whether markers of cartilage synthesis and degradation could provide such quantitative measures.Methods. Serum samples from 23 patients receiving infliximab treatment for AS were obtained at baseline and at weeks 2, 6, 14, and 22. Conclusi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 46 publications
(27 citation statements)
references
References 19 publications
1
26
0
Order By: Relevance
“…A previous study of 23 patients with AS demonstrated elevated levels of CPII and 846 epitope in patients with concomitant peripheral synovitis, which supports this hypothesis (23). However, increased osteoclast activation has been documented in animal models of AS (35) and bone resorption markers are increased in AS, particularly in patients with active disease (36,37).…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…A previous study of 23 patients with AS demonstrated elevated levels of CPII and 846 epitope in patients with concomitant peripheral synovitis, which supports this hypothesis (23). However, increased osteoclast activation has been documented in animal models of AS (35) and bone resorption markers are increased in AS, particularly in patients with active disease (36,37).…”
Section: Discussionmentioning
confidence: 59%
“…Some of these biomarkers have been shown to be sensitive and specific for early cartilage changes associated with isolated joint injury in an experimental model of osteoarthritis (OA) (22). A previous study showed that patients with AS demonstrated significant elevations in serum levels of CPII, the 846 epitope, and the CPII:C2C ratio, compared with normal controls (23).…”
mentioning
confidence: 99%
“…MMP‐3 was selected as it degrades other minor proteins in tendon matrix, including collagens III, IV, IX, and X, and also proteoglycans and elastin 28, 29, 30, 31, 32, 33. The C1,2C (or COL 2 3/4C short) antibody detects the carboxy terminus of fragmented type I and II collagen, cleaved by collagenases MMP‐1, MMP‐8 or MMP‐13 21, 34, 35, 36, 37…”
Section: Methodsmentioning
confidence: 99%
“…Biomarkers reflecting type II collagen degradation include Col2-3/4 (long mono) (C2C) and CTX-II. CPII, 846 epitope, and the CPII/C2C ratio have been reported as increased at baseline in AS, but only the CPII/C2C ratio correlated with CRP in patients receiving infliximab [25]. A decrease in C2C was shown to correlate with the reduction in CRP and ESR levels in patients receiving etanercept [24].…”
Section: Biomarkers Indirectly Reflecting Inflammationmentioning
confidence: 97%